2019
DOI: 10.1149/2.0981913jes
|View full text |Cite
|
Sign up to set email alerts
|

A Wide Range of Testing Results on an Excellent Lithium-Ion Cell Chemistry to be used as Benchmarks for New Battery Technologies

Abstract: We present a wide range of testing results on an excellent moderate-energy-density lithium-ion pouch cell chemistry to serve as benchmarks for academics and companies developing advanced lithium-ion and other "beyond lithium-ion" cell chemistries to (hopefully) exceed. These results are far superior to those that have been used by researchers modelling cell failure mechanisms and as such, these results are more representative of modern Li-ion cells and should be adopted by modellers. Up to three years of testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
325
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(335 citation statements)
references
References 30 publications
4
325
0
1
Order By: Relevance
“…First, degradation models can be outdated because all degradation models need to be fitted based on the experimental battery data which has changed hugely over the years due to the advancement in battery materials. For example, the capacity fade in a more recent work for the NMC battery cell can be only around 7% after 4500 cycles and less than 1% after 450 day [74]. Second, a battery asset owner can utilise the battery to provide many other different ancillary services which is not considered in this study.…”
Section: Discussionmentioning
confidence: 95%
“…First, degradation models can be outdated because all degradation models need to be fitted based on the experimental battery data which has changed hugely over the years due to the advancement in battery materials. For example, the capacity fade in a more recent work for the NMC battery cell can be only around 7% after 4500 cycles and less than 1% after 450 day [74]. Second, a battery asset owner can utilise the battery to provide many other different ancillary services which is not considered in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Taking structural instability of the spherical secondary structure and large surface area of the nanosized primary particles into consideration, single‐crystal materials are in principle beneficial to stabilizing the performance of the layered cathode. For example, Harlow et al demonstrated that in a wide temperature range (20∼55 °C), the Li‐ion cells employing single‐crystal NMC532 provide far longer lifetimes when compared with cells using spherical aggregates. The increased lifetime is attributed to two properties of the single‐crystal materials: (1) intrinsically better stability of the single‐crystal primary structure compared to the spherical secondary structure, and (2) significantly smaller specific surface area of the large single‐crystals compared to the nanosized primary particles.…”
Section: Challenges and Strategiesmentioning
confidence: 99%
“…However, it is likely that they will be changed before they reach the 80% threshold not because they do not work properly but because there are other battery technologies and chemistries that will get better in the near future. For example, a recent study by Professor Jeff Dahn's group at Dalhousie University and Tesla Canada presented a LIB testing benchmark where they included a battery with a lifetime of around 4600 cycles (1.600,000 km driving range), at extreme discharging conditions (i.e., bringing the battery to a full discharge in each cycle), which could also be employed in energy storage for 20 years after reaching its EV end of life [20]. Still, even if novel batteries will get more cost-effective and safer, the battery manufacturing processes remain energyintensive [21].…”
Section: Introductionmentioning
confidence: 99%